2020
DOI: 10.3758/s13428-020-01431-2
|View full text |Cite
|
Sign up to set email alerts
|

Magic Curiosity Arousing Tricks (MagicCATs): A novel stimulus collection to induce epistemic emotions

Abstract: There has been considerable interest in empirical research on epistemic emotions, i.e., emotions related to knowledge-generating qualities of cognitive tasks and activities such as curiosity, interest, and surprise. One big challenge when studying epistemic emotions is systematically inducting these emotions in restricted experimental settings. The current study created a novel stimulus set called Magic Curiosity Arousing Tricks (MagicCATs): a collection of 166 short magic trick video clips that aim to induce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 51 publications
2
29
0
Order By: Relevance
“…The results showed that the correlations between them are at a moderate-level withinperson. These results are consistent with previous studies examining within-person relationship between curiosity and interest using distinct stimuli (e.g., trivia questions; Fastrich et al, 2018;Ozono et al, 2020) and provide convergent evidence that curiosity and interest represent distinct subjective feelings, or in other words, have unique aspects with some overlap.…”
Section: The Closeness and Heterogeneity Of Correlations Between Intesupporting
confidence: 91%
“…The results showed that the correlations between them are at a moderate-level withinperson. These results are consistent with previous studies examining within-person relationship between curiosity and interest using distinct stimuli (e.g., trivia questions; Fastrich et al, 2018;Ozono et al, 2020) and provide convergent evidence that curiosity and interest represent distinct subjective feelings, or in other words, have unique aspects with some overlap.…”
Section: The Closeness and Heterogeneity Of Correlations Between Intesupporting
confidence: 91%
“…Regardless of the precise nature of the interaction between reward and curiosity, our findings suggest that intrinsic motivation to learn from curiosity leads to an almost identical increase in the probability of correctly recalling a trivia answer as extrinsic motivation from reward. Therefore, interventions aimed at enhancing memory and learning outcomes can target intrinsic motivation states (e.g., curiosity, interest, satisfaction, and surprise; Ozono, et al, 2020; Ryan & Deci, 2000;) instead of extrinsic contingencies of reinforcement (e.g., monetary bonuses, testing grades; Slavin, 2010; Stan, 2012)…”
Section: Discussionmentioning
confidence: 99%
“…In empirical work, researchers have traditionally relied on experimental approaches, with the main focus on short-term (mostly one-shot) information-seeking behavior or associated momentary feelings. In fact, common experimental paradigms used to empirically examine curiosity are gambling tasks that provide participants with the opportunity to “peek” at the outcome of a gamble that cannot be changed (e.g., Blanchard et al, 2015; Bennett et al, 2016; Rodriguez Cabrero et al, 2019); or a series of textual or visual stimuli aimed to trigger momentary feelings of curiosity on a trial-by-trial basis, such as trivia questions (McGillivray et al, 2015), blurred images (Jepma et al, 2012), and magic tricks (Ozono et al, 2020).…”
Section: Comparison Of Research On Curiosity Interest and Traitsmentioning
confidence: 99%